Real-world treatment patterns and effectiveness of palbociclib plus an aromatase inhibitor in patients with metastatic breast cancer aged 75 years or older - Brufsky, Adam; Liu, Xianchen; Li, Benjamin; McRoy, Lynn; Chen, Connie; Layman, Rachel M.; Rugo, Hope S. (Frontiers in Oncology, 2023)
Background: Elderly patients are generally underrepresented in oncology clinical trials; therefore, real-world data are needed to inform clinical management of elderly patients with hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2−) metastatic breast cancer (mBC). This subanalysis of the P-REALITY X study (NCT05361655) evaluated palbociclib treatment patterns and comparative effectiveness of palbociclib plus an aromatase inhibitor (AI) versus an AI alone among patients with HR+/HER2− mBC aged ≥ 75 years treated in routine clinical practice in the United States.Methods: This retrospective observational cohort study used electronic health records from the Flatiron Health Analytic Database. Palbociclib treatment patterns, overall survival (OS), realworld progression-free survival (rwPFS), and time to chemotherapy (TTC) were evaluated.Three methods were used for comparative analyses: (1) an unadjusted analysis, (2) stabilized inverse probability treatment weighting (sIPTW; primary analysis), and (3) propensity score matching (PSM; sensitivity analysis).Results: A total of 961 patients aged ≥ 75 years with HR+/HER2− mBC were identified who started palbociclib plus an AI (n = 313) or an AI alone (n = 648) as first-line (1L) therapy between February 2015 and March 2020 (data cut-off: September 30, 2020). Among patients in the palbociclib plus an AI group with a documented palbociclib starting dose (n = 306), approximately 75% started palbociclib at 125 mg/day, and approximately 40% experienced dose adjustment. After sIPTW, patients treated with palbociclib plus an AI versus an AI alone had significantly improved OS (median of 43.0 vs. 32.4 months; hazard ratio [HR], 0.66 [95% confidence interval (CI), 0.51-0.84]; P = 0.0007), rwPFS (median of 20.0 vs. 15.0 months; HR, 0.72 (0.59-0.89); P = 0.0021), and TTC (median of 40.2 vs. 27.4 months; HR, 0.69 [0.55-0.87]; P = 0.0014). These significant improvements in OS, rwPFS, and TTC remained consistent in the unadjusted analysis and after PSM.This real-world comparative analysis demonstrated that 1L palbociclib plus an AI is associated with improved effectiveness compared with an AI alone among patients with HR+/HER2− mBC aged ≥ 75 years. These findings support palbociclib plus an AI as a standardof-care 1L treatment for elderly patients with HR+/HER2− mBC.